Congenital primary hypoparathyroidism presented with extensive cutaneous and subcutaneous calcifications - Aslan, Yakup; Gedik, Yusuf; Ökten, Ayşenur; Aksoy, Ayşe; Çimşit, Gülseren; Ari, Nurcihan (The Turkish Journal of Pediatrics, 1999)
Congenital primary hypoparathyroidism is very rare in infancy. It may be isolated or associated with other developmental defects, arising from the third and fourth pharyngeal pouches such as DiGeorge syndrome. Initial symptom of isolated primary hypoparathyroidism in an infant is usually generalized convulsion due to hypocalcemia. However, the clinical spectrum of DiGeorge’s anomaly is highly variable. We report a two-hour-old neonate with congenital hypoparathyroidism presenting with extensive cutaneous and subcutaneous calcifications. To our knowledge, extensive calcification of the skin and subcutaneous tissue as a presenting feature of congenital primary hypoparathyroidism in an infant is reported for the first time.